N-3 Polyunsaturated Fatty Acids Supplementation Does not Affect Changes of Lipid Metabolism Induced in Rats by Altered Thyroid Status - Rauchová, H.; Vokurková, M.; Pavelka, S.; Behuliak, M.; Tribulová, N.; Soukup, T. (Hormone and Metabolic Research, 2013)
Epidemiological studies have demonstrated that n-3 polyunsaturated fatty acid (PUFA) consumption is associated with a reduced risk of atherosclerosis and hyperlipidemia. It is well known that lipid metabolism is also influenced by thyroid hormones. The aim of our study was to test whether n-3 PUFA supplementation (200 mg/kg of body weight/day for 6 weeks given intragastrically) would affect lipid metabolism in Lewis male rats with altered thyroid status. Euthyroid, hypothyroid, and hyperthyroid status of experimental groups was well defined by plasma levels of triiodothyronine, the activity of liver mitochondrial glycerol-3-phosphate dehydrogenase, and by relative heart weight. Fasting blood glucose levels were significantly higher in the hyperthyroid compared to the euthyroid and hypothyroid rats (5.0±0.2 vs. 3.7±0.4 and 4.4±0.2 mmol/l, respectively). In hyperthyroid animals, the concentration of plasma postprandial triglycerides was also increased compared to euthyroid and hypothyroid rats (0.9±0.1 vs. 0.5±0.1 and 0.4±0.1 mmol/l, respectively). On the other hand, hypothyroidism compared to euthyroid and hyperthyroid status was associated with elevated plasma levels of total cholesterol (2.6±0.2 vs. 1.5±0.1 and 1.6±0.1 mmol/l, respectively), LDL cholesterol (0.9±0.1 vs. 0.4±0.1 and 0.2±0.1 mmol/l, respectively) as well as HDL cholesterol (1.6±0.1 vs. 1.0±0.1 and 1.3±0.1 mmol/l, respectively). Supplementation of n-3 PUFA in the present study did not significantly modify either relative heart weight or glucose and lipid levels in any thyroid status.
Keywords: hypothyroidism; hyperthyroidism; mitochondrial glycerol-3-phosphate dehydrogenase; glucose; plasma lipids